Effect of Planting Distance and Harvest Date on Some Morphological Characteristics of Pea Crop (Pisum sativum L. var. Douce provence) - Aisha Ellafi,; Omar Altoome,; Aisha Faraj Jarbou, (African Journal of Advanced Pure and Applied Sciences, 2025)
This study was conducted at the National Center for Multiplication and Marketing of Improved Seeds, Sidi Al- Masry, Tripoli, Libya. To study the effects of planting distances between plants within a single line (10, 20, and 30 cm) and early and late harvest dates and the interaction between them on some morphological characteristics of pea crop. Pisum sativum var. Douce provence. According to the design of Completely Randomized Blocks (R. C. B. D) with three replications, examining two factors planting distance and harvest date early and late. The measured traits included plant height, final node number, branch number, pod number, seed number per pod, and pod length. The results of research showed that increasing the planting distances between plants from 10 to 30 cmled significantly (P≤0.01) to an increase in the average number of branches, pods and seeds per plant, which were 3.4 branches/plant, 19.4 pods/plant,101.3 seeds/plant, respectively. The results showed that the planting distances had a significant effect on the average plant height and length of one pod, as the highest plant height was reached of 10cm, which was 62.0cm, while the longest pod was reached at longest pod was reached at a distance of 30cm, which was 7.3cm. The results showed that the planting distance between plants did not have any significant effect on the average number of seeds per pod, pod width, and number of terminal nodes per plant, while the harvest date had a significant effect on the average number of branches and pods and plant heigher at late harvest 3.4 branches/plant,16.2 pods/plant and 69.3 cm compared to early harvest respectively